Kinetics of tapioca slurry saccharification process using immobilized multi-enzyme system enhanced with Sg. Sayong clay / Siti Noraida Abd Rahim, Alawi Sulaiman and Nurul Aini Edama - Abd Rahim, Siti Noraida; Sulaiman, Alawi; Edama, Nurul Aini (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
In this paper, immobilization of multi-enzyme using calcium alginate-clay beads for tapioca slurry saccharification process was carried out. The kinetics parameter and immobilization yield for alpha-amylase, glucoamylase, cellulose and multi-enzyme system were compared. The Michaelis constant, Km for free alpha-amylase, glucoamylase, cellulase and multi-enzyme were 2.0831,1.8326, 7.8592 and 3.5367 mg/mL, respectively. As for the immobilized system, the Km values were 3.1604, 2.1708, 9.2791 and 4.91176 mg/mL, respectively. The Km value for the immobilized multi-enzyme system was 1.39 times higher than free multi-enzyme system. This suggests that the immobilized multi-enzyme is a potential system for tapioca saccharification process due to affinity of enzyme to the substrate. For the immobilization yield, the yield for alpha-amylase, glucoamylase, cellulase and multi-enzyme were 51.19, 50.21, 40.68 and 53.71 %, respectively. The result showed the immobilized multi-enzyme had a higher yield compared to the single enzyme which could be explained due to the synergistic action of alpha-amylase, glucoamylase and cellulose enzymes. Therefore, it can be concluded that the use of immobilized multi-enzyme system had a very good potential for starch bioconversion into glucose.